Assessment of concrete bridges - Structural capacity : Experiences from full-scale testing to failure of a bridge in Kiruna - Bagge, Niklas; Nilimaa, Jonny; Sas, Gabriel; Blanksvärd, Thomas; Bernspång, Lars; Täljsten, Björn; Carolin, Anders; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och brand, 2017)
To calibrate methods for condition assessment of prestressed concrete (PC) bridges, tests were carried out on a 55 year old five-span bridge with a length of 121 m in Kiruna in northern Sweden. Both non-destructive and destructive full-scale tests were performed. This paper presents results regarding methods for assessment of the structural capacity of concrete bridges.